The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1101/2020.05.18.101790
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glycosaminoglycans are specific endosomal receptors forYersinia pseudotuberculosisCytotoxic Necrotizing Factor

Abstract: The Cytotoxic Necrotizing Factor Y (CNFY) is produced by the gram-negative, enteric pathogen Yersinia pseudotuberculosis. The bacterial toxin belongs to a family of deamidases, which constitutively activate Rho GTPases, thereby balancing inflammatory processes. We identified heparan sulfate proteoglycans as essential host cell factors for intoxication with CNFY. Using flow cytometry, microscopy, knockout cell lines, pulsed electron-electron double resonance and bio-layer interferometry, we studied the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
2
0
0
Order By: Relevance
“…The respective segment is significantly different in CNF Y (Fig EV1), which may explain why CNF Y does not interact with Lu/BCAM. Instead, a recent study has shown that a C‐terminal fragment of CNF Y (residues 709–1,014) employs glycosaminoglycans as receptors and is sufficient for endosomal uptake (preprint: Kowarschik et al , 2020), in line with the observations made here. Thus CNF Y , similar to CNF1 (Piteau et al , 2014; Reppin et al , 2017), contains two distinct host cell binding sites, one each at the N‐ and C‐terminus.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The respective segment is significantly different in CNF Y (Fig EV1), which may explain why CNF Y does not interact with Lu/BCAM. Instead, a recent study has shown that a C‐terminal fragment of CNF Y (residues 709–1,014) employs glycosaminoglycans as receptors and is sufficient for endosomal uptake (preprint: Kowarschik et al , 2020), in line with the observations made here. Thus CNF Y , similar to CNF1 (Piteau et al , 2014; Reppin et al , 2017), contains two distinct host cell binding sites, one each at the N‐ and C‐terminus.…”
Section: Resultssupporting
confidence: 86%
“…The receptor of the N‐terminal part of CNF Y is still unknown, but it has been shown that binding of CNF1 to host cells has no effect on CNF Y uptake (Blumenthal et al , 2007), suggesting that both toxins use different host cell factors for endocytosis. This has also been corroborated in a recent study that identified glycosaminoglycans as interaction partners of C‐terminal fragments of CNF Y (preprint: Kowarschik et al , 2020). The CNFs are taken up into endosomes and their release into the host cytoplasm requires two hydrophobic sequence motifs within the N‐terminal half of the toxin that have been predicted to form α‐helices.…”
Section: Introductionsupporting
confidence: 63%